THEORETICAL CALCULATION OF THERMODYNAMIC PROPERTIES AND DIFFUSION COEFFICIENTS FOR PURE ETHANOL, PURE WATER AND BINARY MIXTURE OF (ETHANOL + WATER) AS FUNCTION OF TEMPERATURE BY MOLECULAR DYNAMIC SIMULATION - SOHREVARDI, Nahid; KIANI, Farhoush; KOOHYAR, Fardad (Studia Universitatis Babeș-Bolyai Chemia, 2018)
In this research work, we presented the results of theoretical calculations for the change of thermodynamic properties such as enthalpy ∆H, entropy ∆S, heat capacity ∆Cp, and Gibbs free energy ∆G, for pure water, pure ethanol and interaction of mixture (50% water + 50% ethanol) and binary mixture of (water + ethanol) under thermal equilibrium condition at T = (273.15, 283.15, 293.15, 298.15, 305.15, 311.15, 320.15, 333.15) K and at atmospheric pressure. This theoretical calculation was done using Molecular Dynamic (MD) simulation. The results show that the values of ∆H and ∆S increase and also value of ∆Cp decreases by temperature growth. The obtained value of change of Gibbs free energy for interaction of mixture (50% water + 50% ethanol) shows that this interaction is possible at T = (298.15, 311.15, 320.15, 333.15) K. Also, it showed that the self-diffusion coefficient and the mutual diffusion coefficients increase by increasing temperature.